Cummon National Curriculum Base and transformations in the field of natural sciences and tecnologies (Research, Society and Development, 2020)
This article portrays an enlightening view of the Brazilian scenario in the educational context. It is noticed that education is undergoing many changes and this has been happening for years, however, the current political conjuncture is with new proposals for education reforms. This article will address these changes and their possible consequences. Its main objectives are to analyze the guidelines of the Common National Curriculum Base (BNCC) for High School, identify the contents of the Chemistry discipline that will be removed from the curriculum and the possible social transformations that this change will generate. For such discussions, a theoretical study was carried out on the BNCC, as well as chemistry textbooks that could prove the impoverishment of the chemistry content in the base. It was found that some specific contents were excluded so that transdiciplinarity could occur between the disciplines of Chemistry, Physics and Biology that make up the area of Natural Sciences and their Technologies.